L’extension récente de la taille des aires marines protégées : une progression des surfaces inversement proportionnelle à leur normativité - François Féral (VertigO, 2011)
Multiplying the creation of marine protected areas and especially large areas is a recent political phenomenon at large scale. Legal content of the areas is often poorly defined and it appears that their normativity is generally quite low, inversely proportional to their size. But these initiatives represent a new step for "law of the sea" by which the maritime states now claim sovereignty over their natural resources through science and environmental protection for State interests. France does not want to stay away from this movement influence strengthened. Despite the creation of the Agency for Marine Protected Areas and Marine Park status, the traditional legal framework of its marine protected areas and the rights of its communities overseas are a handicap in this open competition for control over large ocean spaces.